VARIATIONS OF CONTINENTAL DISCHARGE PATTERN IN SPACE AND TIME: IMPLICATIONS FROM THE LAPTEV SEA CONTINENTAL MARGIN, ARCTIC SIBERIA - Kleiber H.P.; Niessen F. (My University, 2000)
Variations in sediment input and distribution to the Laptev Sea continental margin during the Holocene and Termination I could be identified based on radiocarbon dated magnetic susceptibility logs and sediment thickness in high-resolution seismic profiles. Magnetic susceptibility of surface samples reveals an increased input of magnetic grains to the Laptev Sea deriving from the Anabar and Khatanga river catchments. Exposed magnetite schists and volcanic rocks of the Anabar shield and Putoran Plateau, respectively, function as major source of magnetic material. The distribution of magnetic susceptibility in association with the thickness of the Holocene sediments indicates bottom-current induced sediment transport guided by major submarine valleys on the Laptev Sea shelf. The sites of filled paleoriver channels identified in the seismic profiles suggest that during the Late Weichselian sea-level lowstand river runoff continued through four of the major valleys on the exposed Laptev Sea shelf. The sediments at the top of the lowstand deposits in front of the Anabar-Khatanga valley, represented in the seismic profiles by prograding deltas, are characterized by outstandingly high magnetic susceptibility values. Radiocarbon datings approximate the deposition of these high magnetic sediments between 10 and 13.4 ka. It is suggested that this increased input of magnetic material is related to the deglaciation of the Anabar shield and the Putoran Plateau and thus support their glaciation during marine isotope stage (MIS) 2.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен